Feniks . biuletyn informacyjny RKW NSZZ "Solidarność" w Gorzowie Wlkp., no. 178, 1988 - "Solidarność", [ed. board] (Agencja Wydawnicza "Feniks", 1988)
Creation and circulation: From issue no. 1=190(29.IV.1989) published legally